Production Efficiency Analysis of Dairy Cattle Business in Cisarua Bogor District - Dewi, Intani; Husyairi, Khoirul Aziz; Lidya, Leni; Rahmasari, Liisa Firhani (Green Publisher Indonesia, 2023)
This study aims to analyze the production efficiency of dairy cattle business in Cisarua Bogor District. The research focuses on identifying factors that affect production efficiency and provides recommendations for improving the efficiency of dairy cattle business. The study utilizes a quantitative research approach and collects data through a survey questionnaire administered to dairy cattle farmers in Cisarua Bogor District. The findings of this research contribute to the understanding of the factors influencing production efficiency in the dairy cattle industry. The results highlight the importance of precision feeding, genetic factors, and farmers' skills in promoting production efficiency. The implications of these findings for dairy cattle farmers and recommendations for future research are discussed.